Tanggung Jawab Pemerintah Desa Dalam Bidang Pendidikan Di Desa Lutur Kecamatan Aru Selatan Kabupaten Kepulauan Aru - Sihite, Marni G; Pietersz, Jemmy Jefry; Nendissa, Renny Heronia (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2023)
The study aims to determine the responsibility of the village government in the field of education in Lutur Village. Normative legal research on village government or what is commonly referred to as the village head is supported by village officials as one of the elements of village government administration. The village head is a village official who has the authority, obligations and responsibilities to manage his village. Details of the position, duties and function of these community leaders based on domestic regulation number 84 0f 2015 as stipulated in article 6 the village administration who leads the administration of the village. The formulation of the problem to answer this question above is first whether the village government is responsible in the filed of education, seond what are the legal consequences does not carry out its responsibilities. The method used is normative law based on research conducted, the village government is responsible for carrying out development in the filed of education and is legally following.